2012
DOI: 10.1159/000342254
|View full text |Cite
|
Sign up to set email alerts
|

Do Depression and Educational Attainment Mediate the Association between Ethnicity and Dementia?

Abstract: Introduction: Research shows marked differences in the prevalence of dementia among different ethnic groups. However, there is a relative dearth of studies focusing on how ethnicity may influence dementia. The main aim of the current study is to test potential mediating effects of depression and level of education on the association between ethnicity and dementia. Methods: The sample for this study, consisting of 2,796 community-dwelling elderly people aged 60 years and older, was drawn from a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…As expected, in concordance with previous studies, the findings from this study showed statistically significant association between dementia and age, 3 sex, 21 marital status, 22 educational attainment, 15 ethnicity, 4 and stratum. 23 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, in concordance with previous studies, the findings from this study showed statistically significant association between dementia and age, 3 sex, 21 marital status, 22 educational attainment, 15 ethnicity, 4 and stratum. 23 …”
Section: Discussionsupporting
confidence: 93%
“…Validation of the Malaysian version of GMS-AGECAT against clinical assessment of dementia revealed an overall agreement of 76.2% (n=105) with a moderate kappa value of 0.502. 4 The GMS-AGECAT has been widely used and applied with good levels of agreement in a variety of settings. The scores of 3 or higher on the GMS-AGECAT were considered as dementia.…”
Section: Methodsmentioning
confidence: 99%
“…Socio-demographic confounding factors contributing to cognitive function [26,27], such as age, sex, marital status, years of education, household income, and employment status were assessed.…”
Section: Confounding Factorsmentioning
confidence: 99%
“…We included data on birth place, which is an important key indicator of socioeconomic status disparities and possibly of genetic predisposition. In addition, previous studies suggest that risk of cognitive impairment differs between Israeli-born and immigrants populations [24,25]. Physical activity was assessed by asking participants "Do you participate in one or more of the following activities such as walking, swimming, jogging, gymnastics, biking, dancing, tennis, gardening and rehabilitation activities" and "How many times per week do you engage in physical activity".…”
Section: Baseline Laboratory Measurementsmentioning
confidence: 99%